Intersubjectivity, intercultural hermeneutics and the recognition of the other – theoretical reflections on the understanding of alienness in human geography research - Rothfuss, Eberhard (ERDKUNDE, 2009)
Communication in the intercultural context of geographical (development) research is defined by a specific intersubjective relation between the researcher and the researched. It always faces the danger of misinterpretation concerning the actions of the ‘other’. Without the cultural and social differences that affect understanding and thus limit comprehension, the interpretation of research findings remains dubious. The article draws attention to this issue, which, so far, has not received sufficient recognition in human geography. It is a ‘self-experiment’, in the sense of Bourdieu, regarding the asymmetric relation between two subjects from specific and highly dissimilar backgrounds, found in a peculiar situation defined as ‘field research’. With this self-experiment, the possibilities and limits of intercultural hermeneutics are evaluated. Central to the argument is the critical discussion of the socio-philosophical conceptual foundation on which intersubjectivity and interculturality are based. This critique follows a perspective of the theory of recognition that understands the practices and perceptions of the other in the particular context of everyday life, in order to base the analysis of rationalities underlying social action on their understanding.